التوافق الثقافي وعلاقته بتحصيل اللغة العربية بوصفها اغة ثانية لدى متعلميها غير الناطقين بها في المملكة العربية السعودية = al-tawafuk al-saqafi wa 'alaqatuhu bi tahsil al-lughah al-arabiyyah bi wasfiha lughah thaniyah lada muta'allimiha ghair al-natiqina biha fi al-mamlakah al-arabiyyah al-saudiyyah - Salih al-Aboud , Ibrahim; Mamat , Arifin (2015)
This study aimed to identify the level of cultural accommodation through it aspects (social, psychological and academic) students at the Institute of Arabic Language at the Islamic University, and the relationship between that accommodation and the language acquisition. The main problem of this study has been identified through this question: What is the degree of the cultural accommodation among the Arabic language learners, and is there a relationship between that cultural accommodation and the language acquisition? To answer the questions of the study the researcher will use a questionnaires designed for this purpose, and the resolution will be applied on a random sample of students from the third and fourth levels of the Arabic language institute. In the study by the procedures, the researcher will use (SPSS) program to conduct statistical analysis, and in order to get the results of the questionnaires, according to the following stages: First, to answer the question: What is the degree of the cultural accommodation among the Arabic language learners? The research will be a quantitative research, and the researchers will use the (Simple Descriptive Statistical Analysis) which has a distribution account duplicates (Frequency Distribution) and percentages (The percentages) and averages and standards deviations. Second, to answer the question: is there a relationship between that cultural accommodation and the language acquisition? The researchers will use the (Inferential Statistical Analysis), which contains an analysis of variance (ANOVA); to see if there statistically significant differences in the students' responses.